Factors Affecting Acceptance and Non-Acceptance of Covid-19 Vaccination: A Systematic Review Study - Erfan Pourshahri; Meisam Dastani; Matineh Khoshkhoo; Amirhosein Sharghi; Saeed Yaghoubi; Leila Sadeghmoghadam (Mazandaran University of Medical Sciences, 2022)
Introduction and purpose: The identification of barriers and concerns regarding the acceptance of the Covid-19 vaccine is of paramount importance. Accordingly, this systematic review was conducted to determine the factors affecting the acceptance and non-acceptance of the Covid-19 vaccine. Methods: This systematic review was performed in accordance with the principles of Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). The data were retrieved from PubMed, WOS, and Scopus in May  2021. The inclusion criteria entailed: 1- All original articles published on the reasons for acceptance or non-acceptance of the Covid-19 vaccine and 2- English language articles. On the other hand, the exclusion criteria were as follows: 1- Overlap of some articles in several databases, 2- The non-original articles, such as review articles or letters to editors, 3- unrelatedness to the objectives of the study, and 4- Lack of access to the full text of the articles. Results: The query yielded a total of 442 articles. After removing duplicates, as well as screening and qualitative evaluation of articles, 75 articles were finally selected for review in this study. Based on the obtained results, gender in individual factors, trust in governments, hospitals in social factors, and concerns about vaccine side effects among vaccine-related factors played the most important roles in accepting and rejecting the vaccination. Conclusion: Removing barriers to vaccination based on individual, social, and vaccine factors, as well as informing people about its benefits should be a priority for health organizations and institutions. Consequently,  education and information campaigns on vaccination outcomes should be established at the community level to address individual and social concerns, as well as vaccine-related concerns.